Predicting severity of head collision events in elite soccer using preinjury data: a machine learning approach - Tarzi, G.; Tarzi, C.; Saha, A.; Cusimano, M. D. (Clinical Journal of Sport Medicine, 2023)
Objective: To develop machine learning (ML) models that predict severity of head collision events (HCEs) based on preinjury variables and to investigate which variables are important to predicting severity.